PENINGKATAN KUALITAS KOPI MELALUI TEKNOLOGI PASCAPANEN KELOMPOK TANI MEKAR SARI, DI DESA KEMAWI, KECAMATAN SOMAGEDE, KABUPATEN BANYUMAS - Ratnaningsih, Hanim Rahayuani; Rahmawan, Hatika; Hanifa, Hana; Purwanto, Purwanto; Bayyinah, Lafi Na'imatul; Syrifah, Riska Naila Khusna; Sevirasari, Nindy; Hidayati, Wilujeng (Universitas Mataram, 2025)
Coffee is one of Indonesia’s leading plantation commodities that plays an important role in the national economy. However, the quality and productivity of smallholder coffee remain low due to limited post-harvest facilities and farmers’ lack of knowledge. Kemawi Village, Somagede District, Banyumas Regency, has great potential for robusta coffee development, yet post-harvest processing is still carried out traditionally, resulting in inconsistent quality and low added value. This community service program aimed to improve the quality and added value of coffee through the application of post-harvest technology in the Mekar Sari Farmer Group. The method applied a participatory approach, involving observation and field surveys, coordination, counseling, training, and practical assistance in post-harvest processing using pulper and huller machines. Evaluation was conducted through pre-tests and post-tests to measure knowledge improvement, as well as field observations of practical implementation. The results showed an increase in farmers’ knowledge and skills in selective harvesting, controlled fermentation, optimal drying, and proper storage and packaging. Partner farmers were able to operate post-harvest machines independently, which improved processing efficiency and resulted in more consistent coffee quality. Furthermore, the economic value of coffee also increased as the products could be marketed with higher quality. In conclusion, the application of simple post-harvest technology successfully enhanced the quality, efficiency, and competitiveness of robusta coffee in Kemawi Village. Keywords: robusta coffee, post-harvest technology, Mekar Sari Farmer Group, counseling, Banyumas